Hybrid materials based on a layered zinc hydroxide solid and gallic acid: Structural characterization and evaluation of the controlled release behavior as a function of the gallic acid content - Ruiz Madronero, Christhy; et al. (Applied Clay Science, 2019)
The formation of hybrid compounds from gallic acid immobilized into a layered zinc hydroxide is reported. Elemental analysis, X-Ray diffraction, X-ray thermo-diffraction analysis, FT-IR spectroscopy, scanning electron microscopy, and X-Ray photoelectron spectroscopy allowed to identify clear differences between the hybrid materials obtained depending on the gallate anion content within the inorganic matrix. The elemental analysis showed a reduction in the zinc content while a lower d-value was exhibited in the XRD pattern for the material with the highest gallate anion content. With these results was evidenced a structural transformation from a Zn5(OH)8(NO3)2·2H2O type phase to a layered Zn3(OH)4(NO3)2 type phase when the gallate anions entirely replaced the nitrate anions. The formation of the latter phase at room temperature has not previously been reported. The final hybrid compound with a formula of Zn3(OH)4(C7H6O5)2, shows an interlayer space of 7.7 Å in comparison to 7.0 Å for the Zn3(OH)4(NO3)2 phase, which suggests an arrangement of the organic molecule with a parallel orientation to the y-axis. The X-ray diffraction patterns as a function of temperature showed that a completed incorporation of the gallate anion into the material increased over a 200 °C range (from 150 to 350 °C), the temperature for the decomposition of the layered phase to ZnO. The organic-inorganic materials synthesized using gallic acid as a guest and a layered zinc hydroxide as a host matrix can act as controlled delivery and storage systems. The release of gallate anions was found to be concentration-dependent with a release mechanism described by the Elovich and Freundlich models.<br